2006
DOI: 10.1038/sj.gt.3302868
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic RNA interference of malignant melanoma by electrotransfer of small interfering RNA targeting Mitf

Abstract: Microphthalmia-associated transcription factor (Mitf) is critically involved in melanin synthesis as well as differentiation of cells of the melanocytic lineage. Some earlier studies suggested that Mitf is also essential in the survival of melanoma cells, but this notion remains controversial. We synthesized short interfering RNA (siRNA) duplexes corresponding to the mitf sequence and transfected them into B16 melanoma. Lipid-mediated transfection in vitro of Mitfspecific siRNA resulted in specific downregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 71 publications
(74 reference statements)
2
58
0
Order By: Relevance
“…Moreover, EP has proven to be an efficient method for in vitro and in vivo delivery of siRNA/shRNA molecules into tumor cells resulting in successful silencing of reporter or therapeutic genes, including K-ras. 11,[33][34][35][36] Previous in vivo study performed on pancreatic tumors showed that electrotransfection of subcutaneous or orthotopic pancreatic tumors (Panc-1) with synthetic siRNA or plasmid DNA encoding shRNA directed against K-ras dramatically reduced the tumor growth. 11 Results obtained from pancreatic tumor model and our results are consistent with the observation that a single electrotransfection of colorectal tumors with pmiRNA-Kras resulted in growth delay of 8 days, whereas in the study by Rejiba et al 11 the growth delay of 15 days was achieved after two consecutive electrotransfections of pancreatic tumors with pshRNA-K-ras (time interval: 7 days).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, EP has proven to be an efficient method for in vitro and in vivo delivery of siRNA/shRNA molecules into tumor cells resulting in successful silencing of reporter or therapeutic genes, including K-ras. 11,[33][34][35][36] Previous in vivo study performed on pancreatic tumors showed that electrotransfection of subcutaneous or orthotopic pancreatic tumors (Panc-1) with synthetic siRNA or plasmid DNA encoding shRNA directed against K-ras dramatically reduced the tumor growth. 11 Results obtained from pancreatic tumor model and our results are consistent with the observation that a single electrotransfection of colorectal tumors with pmiRNA-Kras resulted in growth delay of 8 days, whereas in the study by Rejiba et al 11 the growth delay of 15 days was achieved after two consecutive electrotransfections of pancreatic tumors with pshRNA-K-ras (time interval: 7 days).…”
Section: Discussionmentioning
confidence: 99%
“…As it has been already proven in previous studies, this limitation might be overcome by repeated administration of silencing molecules. 11,[36][37][38] The repetitive treatments might be important for the eradication of tumor cells that fail to be transfected in a single treatment. For repetitive therapies, it is important that gene delivery method is safe and that it can be applied locally, which are both undoubtedly the advantages of EP.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, inhibition of MITF expression induces a G 0 -G 1 growth arrest of melanoma cells (5)(6)(7). MITF has been also involved in the control of melanoma survival through the control of BCL2 or BIRC7 (8,9), but MITF silencing only marginally causes apoptosis (8,10). In addition to apoptosis, senescence is another cellular failsafe program that counteracts excessive mitogenic signaling observed in cancer cells.…”
Section: Introductionmentioning
confidence: 91%
“…Loss of MITF function, either by siRNA knockdown or expression of a dominant negative allele, leads to reduced melanoma growth and decreased melanocyte cell viability (25,40). If regulation of ML-IAP expression by MITF is required for melanoma cell viability, then overexpression of ML-IAP from a constitutive promoter should be able to rescue MITF siRNA-induced cell death.…”
Section: Mitf Is a Candidate Transcriptional Regulator Of Ml-iapmentioning
confidence: 99%